Adolescents eating behavior, body image and psychological well-being - Peternel, Lana (Array, 2009)
Abstract: This study focuses on the middle school students in the Croatian region of Dalmatia. The survey was designed to examine adolescent eating behavior as it relates to body image and psychological well-being (self-esteem, life-satisfaction and stress) in relation to body mass index, BMI. Differences among participants in food intake were examined according to demographic variables and eating behavior (regular food intake or dieting) as well. Psychological variables were highly associated with dieting among adolescents of both genders. The adolescents who were dieting reported significantly lower self-esteem, lower life satisfaction and lower body-image satisfaction, higher rate of stress and higher rate of body mass index (BMI) when compared to non-dieters. This study confirms that a rather large percentage of adolescent girls of low socioeconomic status engage in dieting when trying to lose weight, which may seriously damage their developmental growth